Acoustic wayfinding: A method to measure the acoustic contrast of different paving materials for blind people. (January 2017) - Secchi, Simone; Lauria, Antonio; Cellai, Gianfranco
Abstract: Acoustic wayfinding involves using a variety of auditory cues to create a mental map of the surrounding environment. For blind people, these auditory cues become the primary substitute for visual information in order to understand the features of the spatial context and orient themselves. This can include creating sound waves, such as tapping a cane. This paper reports the results of a research about the "acoustic contrast" parameter between paving materials functioning as a cue and the surrounding or adjacent surface functioning as a background. A number of different materials was selected in order to create a test path and a procedure was defined for the verification of the ability of blind people to distinguish different acoustic contrasts. A method is proposed for measuring acoustic contrast generated by the impact of a cane tip on the ground to provide blind people with environmental information on spatial orientation and wayfinding in urban places. Highlights: Tapping a cane on a paving is a substitute for visual information in spatial orientation. Analysed the acoustic cues generated by different materials impacted by the blind cane. Introduced a new parameter to describe the acoustic contrast of paving materials. Good correlation with the perception of the signal by a sample of blind people.